Comparison of Calendit -E Cream Versus Expressed Breast Milk - Kazemirad, mehri; Khodakarami, nahid; Salamzadeh, jamshid; Nasiri, navideh; Kazemi, majid; Moattar, fariborz (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: It is estimated that 80-90 % of breastfeeding women experience some nipple injury and soreness, with 26% progressing to cracking and extreme nipple pain that could lead to breastfeed failure. The aim of this study was to examine the effect of Calendit –E cream and expressed of breast milk in the treatment of nipple crack. Materials and methods: This study is a single blind randomized clinical trial. 82 breastfeeding women with age older than 18, who suffered from nipple crack were included in the study . After explaining methods of the study and obtaining written consent, the samples randomly assigned into two groups: Calendit -E cream and expressed breast milk and they were treated for one week. The correct method of breastfeeding and using of cream or mother’s milk were instructed to both groups. The nipple crack scores were measured and recorded by the researcher before treatment and third and seventh days of the study. A questionnaire was used for collecting demographic data, the severity of crack was measured by observing the nipple using Storr score check list , and evaluation form of breastfeeding. Data were analyzed by SPSS software and t-test, paired t-test, chi-square, Mann-Whitney, Wilcoxon and repeated measurement tests. Finding: The statistical tests showed the severity of crack between the two groups, before the study was highly homogeneous the severity of cracks reduced on the third day with no significant difference between two groups (P = 0.2). But in the seventh day this decrease was more significant in the Calendit-E group (p = 0.006). Conclusion: Calendit -E cream is more effective than expressed breast milk on the nipple crack’s treatment. Key Words: Calendit-E cream, Expressed breast milk, Nipple crack, Breastfeeding mother